The Impact of Financial Performance, and Institutional Ownership on Tax Avoidance in the Banking Sector Listed on the Indonesia Stock Exchange - Adhityawati Kusumawardhani; Amalia Indah Pratama Mallisa (International Journal of Organizational Behavior and Policy, 2023)
This study aims to determine the effect of financial performance and institutional ownership on tax avoidance in the banking industry listed on the Indonesia Stock Exchange during the 2017-2021 period. In addition, to find out whether these factors influence tax avoidance efforts made by the banking industry. This study uses quantitative research methodology, using secondary data sources derived from the annual financial statements of the Indonesia Stock Exchange and Refinitiv. This study uses the purposive sampling method to select 25 banking sector companies from 125. The results showed that tax avoidance efforts were influenced by return on assets and leverage. Company size and institutional ownership do not affect tax avoidance efforts. The limitation of this study is that the institutional ownership variable is quite challenging to obtain because it is limited to the company’s annual report, so it is hoped that further research can expand the scope of the study used.